Determining the Effect of COVID-19 Anxiety and Awareness Levels of the Elderly on Fear of Coronavirus - Reha Karakaya; Tuba Özaydın (Hemşirelikte Araştırma Geliştirme Dergisi)

(untitled)
Aim: This study aims to investigate the effect of coronavirus anxiety and awareness levels of elderly individuals on their fear of coronavirus during the pandemic. Methods: The study consists of 227 individuals over the age of 65 who visited the emergency department of a hospital in Turkey between April and December 2021. Data were collected through face-to-face questionnaire administration using the COVID-19 Fear, Anxiety and Awareness Scale. Number, percentage, mean and standard deviation values were calculated for statistical analyses. Since the data showed normal distribution, t-tests and One-Way ANOVA were performed in the analysis for independent groups. In addition, multiple linear regression analysis was performed. Results: A statistically significant difference was found between the level of coronavirus fear and marital status, with whom the elderly live, the number of children, having a chronic disease, and the status of continuous medicine use (p<0.05). It was revealed that the determinants of the level of coronavirus fear are continuous medicine use, the number of children, marital status, coronavirus anxiety score, and infection prevention awareness and awareness of hygiene measures scores (p<0.05). Conclusion: The elderly in this study were found to have moderate levels of coronavirus fear. Home visits regarding anxiety and awareness, monitoring the COVID-19 fear level of the elderly and taking precautions against this fear can reduce the effects of the pandemic on the elderly.